IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH PADA TK NEGERI PEMBINA 2 PALEMBANG - Insan, Amirul (UNISAN JURNAL, 2024)
Educational supervision activities are very necessary for teachers, because for teachers who work every day at school there is no other party who is closer and knows all their activities, except the Principal. Teachers are one of the determining factors for the low quality of educational outcomes. In order to implement an educational supervision program, it must include all components that are related and influence the success of the educational supervision program. This success can be seen from the planning and implementation components of the educational supervision program. The aim of this research is to describe and analyze. Implementation of supervision of learning activities at TK Negeri Pembina 2 Palembang City. Implementation of supervision by the Head of SMP 2 Bangkinang City. The method used in this research is a qualitative approach. Data collection techniques through observation, interviews and documentation. Data sources consist of school principals and teachers at TK Negeri Pembina 2 Palembang. The results of this research indicate that supervision of learning activities is carried out by the school principal in order to improve teacher competence.